Colonization of oil palm empty fruit bunches by basidiomycetes from the Brazilian cerrado: Enzyme production. Issue 4 (15th February 2022) - da Silva, Elias Alves; Mendes, Thais Demarchi; Pacheco, Thályta Fraga; Wischral, Daiana; dos Santos, Dulce Cristine; Mendonça, Simone; Camassola, Marli; de Siqueira, Félix Gonçalves; Souza, Manoel Teixeira
Abstract: The use of residual lignocellulosic biomass appears as an opportunity to obtain high added value products like enzymes. The present work goal was to select basidiomycetes capable of metabolizing empty fruit bunches (EB) or sludge decanter (SD) from the oil palm industry to produce enzymatic cocktails. First, eight macro‐basidiomycetes strains from the Brazilian cerrado were selected based on genomic DNA analyses out of an initial group of 30. The selected basidiomycetes and two ascomycetes (commercial mushrooms) were cultured to obtain ligninolytic and cellulolytic enzymes, respectively. All the extracts produced had proteins, and enzymatic profiles evaluated. The enzymatic hydrolysis of pretreated EB used cocktails of basidiomycetes extracts combined with commercial cellulases or ascomycetes extracts. The best combination of enzymatic extracts for hydrolyses of hydrothermally pretreated EB was the cocktail with Trichoderma reesei, Aspergillus aculeatus, and Pleurotus sp. extracts, reaching 19.7% of glucose yield and 22.8% of xylose yield. These results show that enzymes and sugars are products derivable from residues produced in large quantities by the oil palm industry. This study corroborates the hypothesis that basidiomycetes from the Brazilian cerrado present an enormous biotechnological potential, still unexplored. Abstract : Basidiomycetes produced enzymes from empty bunches of palm oil (EB). Best strains to glucose releasing were Pleurotus sp. and Flavsodon flavus. The mixture with ascomycetes extract resulted in a glucose yield of 19.7% from EB. Fomes fasciatus exhibited the best growth and vigor in solid‐state cultivation.